Adjusting the Concept of the Validity of Worship in the Terminology of the Ushuliyyin - Tw, Afrizal (Journal of Islamic Sciences, 2022)
This study aimed to clarify the reality of the meaning of Sihhah in worship for the theologians and jurists, and to clarify the difference between the theologians and jurists. This study dealt with controlling the concept of Sihhah among Ushuliyyin, and that the fundamental disagreement occurs between the Hanafiyyah and the majority of Ushuliyyin in the definition of Sihhah; due to the difference of opinion between them. The study followed the inductive approach by collecting and tracing the meaning of Sihhah and what is related to it from its original sources. The comparative method was also used by balancing between the opinions of jurists and theologians on the issue of Sihhah and what is related to it, presenting their evidence and discussion, then weighing what the researcher deems most likely. In his study, the researcher concluded that the validity of worship for the theologians is the approval of the two-sided act, obliged qadha and vice versa; because they looked at the suspect or conjecture of the presumptive. As for the Sihhah of worship according to the jurists looked at the true act or factual consent, and they defined authenticity as: what was ajza’ and without qadha; because they looked at Realistic Consent. The difference occurs between these two fundamentals is in pronounciation and naming, And as for legal matters, that they have agreed to make qadha’ obligatory for those who suspect themselves in purity, even though it is proven otherwise, and indeed the persons who performs the prayer gets a reward and it is not obligatory for him to make qadha’ if it is not proven otherwise.